Evaluating the surrounding physical habitat for Thynnichthys thynnoides's spawning areas using a visual-based habitat assessment at Rui River, Perak - Amonodin, Mohamad Radhi; Hashim, Rohasliney; Azmai, Mohammad Noor Amal; Hashim, Zarul Hazrin (Universiti Putra Malaysia Press, 2019)
This study was conducted to evaluate the physical habitat of spawning areas for Thynnicthys thynnoides (T. thynnoides) in the Rui River, Gerik, Perak. Five sampling sites of Rui River's floodplain were chosen. Sampling was conducted between May and October 2015 by using a visual-based habitat assessment developed for Rapid Bioassessment Protocols for Use in Streams and Wadeable Rivers: Periphyton, Benthic Macroinvertebrates and Fish. This study showed that T. thynnoides still migrated to the upper stream of Rui River during spawning season mainly in August. Habitat assessment scoring indicated that the physical habitat structure of Rui River fell into a suboptimal category, which was most likely able to support fish populations and thus providing a suitable habitat for T. thynnoides during the spawning season. Conclusively, it was observed that the T. thynnoides population was dependent on environmental conditions.